Meningkatkan Kemampuan Keuangan: Peran Mediasi Perilaku Keuangan (UMKM) Di Kecamatan Tuah Madani - Rahmi, Fitri; Nesneri, Yessi (Akuntansi dan Manajemen, 2025)
Financial capability is one of the important aspects in the sustainability of MSMEs in order to survive and develop. This study aims to analyze the effect of financial knowledge, financial skills, financial attitudes, and financial inclusion on financial capability with financial behavior as a mediating variable in MSME players in Tuah Madani District, Pekanbaru City. This research uses a quantitative approach with Partial Least Squares - Structural Equation Modeling (PLS-SEM) analysis technique through SmartPLS 4 and a sample of 116 respondents obtained using purposive sampling technique. The results showed that financial knowledge, financial skills, and financial behavior have a significant effect on financial capability. while financial attitudes and financial inclusion have no significant direct effect on financial capability. Financial behavior mediates the relationship between financial knowledge and attitudes towards financial capability. However, financial behavior does not mediate financial skills on financial capability. The R² value of 0.779 indicates that 77.9% of the financial capability variable can be explained by the variables in this model, the remaining 22.1% is influenced by other variables outside this study.